2020
DOI: 10.21203/rs.2.20550/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic of tobacco (Nicotiana tabacum L.) identified major host proteins involved in photosystems throughout the aging process

Abstract: Background: Leaf senescence is one of the most common manifestations in plant senescence and has an important effect on plant photosynthesis. Delaying or shorten the senescence of tobacco leaves is one of the important approaches to improve tobacco breeding. However, the molecular regulatory mechanism of tobacco leaf senescence in response to photosynthesis is still poorly understood. To gain insights into the senescence of tobacco leaves, we integrated analyses including photosynthesis, organelle ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(53 reference statements)
0
1
1
Order By: Relevance
“…Finding decreased emotion regulation to predict more symptoms of oppositional defiant disorder from childhood to adolescence adds to two former investigations revealing such a relation (Mitchison, Liber, Hannesdottir, & Njardvik, 2020;Yu et al, 2021) but runs counter to the null results of two other studies (Chen, He, et al, 2022;Craig et al, 2020). Notably, the latter two had considerably fewer participants than the study by Yu et al (2021) and the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Finding decreased emotion regulation to predict more symptoms of oppositional defiant disorder from childhood to adolescence adds to two former investigations revealing such a relation (Mitchison, Liber, Hannesdottir, & Njardvik, 2020;Yu et al, 2021) but runs counter to the null results of two other studies (Chen, He, et al, 2022;Craig et al, 2020). Notably, the latter two had considerably fewer participants than the study by Yu et al (2021) and the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the above reasoning and findings and the fact that the DSM-5-defined symptoms of ODD have a strong emotional component that points to a tenable link between emotion dysregulation and ODD, this possibility has-to the best of our knowledge-been explored in only two prospective studies with cross-lagged design. One found emotion regulation among children screened high on ODD at age 9 and 10 to be unpredictive of more ODD symptoms at age 10 and 11, respectively (Chen, He, et al, 2022). The other reported that poor emotion regulation in Grade 2 predicted more ODD symptoms in Grade 3 (Yu et al, 2021).…”
Section: Emotion Regulation and Oddmentioning
confidence: 99%